E-Government in Indonesia: Policy Review and Implementation of Jokowi's Government - Junior Hendri Wijaya (TheJournalish: Social and Government, 2023)
The rate of adoption of information and communication technology in government administration, known as E-Government, has become an important issue in the Indonesian context, especially under the leadership of President Joko Widodo (Jokowi). This research aims to provide an in-depth overview of E-Government policies and implementation in Indonesia during Jokowi's administration. Researchers analyzed the policy steps taken by the Jokowi government in advancing E-Government and analyzed the success rate of its implementation. In addition, this study also identifies challenges and obstacles faced in efforts to improve public services through information technology. The results of this study provide a better understanding of the progress of E-Government in Indonesia, its contribution to government efficiency, and its impact on public services. By understanding the extent to which E-Government policies and implementation have been successful, the government and other stakeholders can take further steps to improve this system to achieve a more transparent, inclusive, and effective governance in Indonesia.